Les migrants, sujets de la mobilisation ? L’expérience des migrants équatoriens dans la crise espagnole à la fin des années 2000 - Olga L. González (Les Cahiers ALHIM)
The aim of this article is to study the Ecuadorian migrants struggle to keep their homes and expose abuses of the banking system in the late 2000s in Madrid. From this experience, we want to think about the broader issue of the mobilization of migrants, a topic that has had relatively little attention in the sociological literature. The first part of the article presents this mobilization: initiated in 2008, carried by migrants, it has rebounded with the movement of indignados during the 2011 summer. The second part of the article examines some possible hypothesis about the invisibility of such protests and raises questions about its consequences.